Validity and Reliability of Cadastral Map for Complete Systematic Land Registration in Kalisari and Tlogopandogan Villages, Demak Regency, Indonesia - Nugroho, Tanjung (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
PTSL is a national strategic program aimed at achieving complete land certification in Indonesia. Starting in 2017, it is expected that by the end of 2024, all land parcels will be registered, and a reliable land information system will be established for public services. One of the key components in realizing a reliable land information system is the development of a valid and reliable cadastral map. This study aims to assess the validity and reliability of the cadastral maps created under the PTSL program in Kalisari village and Tlogopandogan village of Demak Regency. The research method employed in this study is a descriptive method based on a quantitative approach. The study is conducted in two PTSL villages, namely Kalisari and Tlogopandogan. PTSL implementation in Kalisari started in 2018, before the issuance of the Complete Systematic Land Registration regulation for the Regency/City in 2019. On the other hand, PTSL implementation in Tlogopandogan commenced in 2020. The validity of cadastral map content was analyzed using Pearson's correlation technique. The reliability of the map was tested using the Cronbach's alpha technique. In general, the findings revealed that the level of validity and reliability of the cadastral map in Kalisari village was assessed as low or less reliable, while the cadastral map in Tlogopandogan village received a high rating in terms of validity and reliability. The high validity and reliability of the cadastral map in Tlogopandogan can be attributed to its adherence to the regulations of the Complete Systematic Land Registration for Regency/City.